Image Repair Efforts of Starbucks PT Sari Coffee Indonesia Amid the Global Pro-Israel Boycott Phenomenon (2023-2024) - Swettie Ayu Calista; Thufailah Nafiisah Bilqis; Theresia Yola Prameswari; Adiasri Putri Purbantina (LPPM Universitas Bina Sarana Informatika, 2026)
This study examines the efforts of Starbucks Indonesia in implementing Image Repair Theory strategies to restore its corporate image following allegations of affiliation with Israel. According to Image Repair Theory, there are three main strategies that organizations can use to repair their image when facing such issues: denial, reduction of offensiveness, and corrective action. This study explains the strategies applied by Starbucks Indonesia using a qualitative descriptive research method through literature review, primary data, and secondary data. The findings indicate that Starbucks Indonesia employs two of these strategies, namely denial through official statements rejecting the allegations, and corrective action through social assistance initiatives such as donations. However, the company still tends to rely on reactive approaches, making it vulnerable to the evolving dynamics of socio-political narratives related to the conflict. While these image repair efforts help mitigate negative reputational impacts in the short term, they are not sufficient to fully ensure long-term consumer trust. Therefore, the company needs to enhance transparency and maintain consistency in its corporate social responsibility practices.